2008
DOI: 10.1099/mic.0.2007/015412-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased d-alanylation of lipoteichoic acid and a thickened septum are main determinants in the nisin resistance mechanism of Lactococcus lactis

Abstract: Nisin is a post-translationally modified antimicrobial peptide produced by Lactococcus lactis which binds to lipid II in the membrane to form pores and inhibit cell-wall synthesis. A nisinresistant (Nis R ) strain of L. lactis, which is able to grow at a 75-fold higher nisin concentration than its parent strain, was investigated with respect to changes in the cell wall. Direct binding studies demonstrated that less nisin was able to bind to lipid II in the membranes of L. lactis Nis R than in the parent strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…These systems can activate enzymes that allow the bacteria to decorate both the cell membrane and cell wall with various chemical modifications. For example, lipid lysinylation of the cellular membrane by MprF (23,44,61,70,77) and D-alanylation of wall teichoic acids by the DltABC locus (15,24,39,41,43,64) provide protection from cationic antimicrobial peptides. Resistance to lysozyme occurs through PG acetylation of MurNAc residues by the OatA O-acetyltransferase found in Gram-positive organisms (3,4,19,34,80) or the PatA/PatB system in Gram-negative organisms (56).…”
Section: Discussionmentioning
confidence: 99%
“…These systems can activate enzymes that allow the bacteria to decorate both the cell membrane and cell wall with various chemical modifications. For example, lipid lysinylation of the cellular membrane by MprF (23,44,61,70,77) and D-alanylation of wall teichoic acids by the DltABC locus (15,24,39,41,43,64) provide protection from cationic antimicrobial peptides. Resistance to lysozyme occurs through PG acetylation of MurNAc residues by the OatA O-acetyltransferase found in Gram-positive organisms (3,4,19,34,80) or the PatA/PatB system in Gram-negative organisms (56).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the activity of truncated nisin mutants showed that nisin-(1-32)-NH 2 , nisin-(1-29) and nisin- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) have respectively slightly higher, about 10-fold lower and 100-fold lower activity than nisin [9]. Rink et al found that nisin-(1-22) has only 10-fold lower activity than nisin and suggested that the positively charged Lys22 might enhance binding to the negatively-charged bacterial membrane [8].…”
Section: Open Accessmentioning
confidence: 99%
“…An interesting candidate antibiotic is the antimicrobial peptide nisin A ( Figure 1) [1]. Although nisin has been widely used for a long time as a food-preservative in a broad range of products [2,3], resistance is limited [4,5]. Nisin is produced by Lactococcus lactis and exerts antimicrobial activity against a broad range of Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial mechanisms of nisin may be due to passage through cell wall and interaction with lipid II [8,9]. Nisin was inhibitory to both Streptococcus thermophilus and Lactobacillus delbrueckii subsp.…”
Section: Introductionmentioning
confidence: 99%